Chronic kidney disease and the alternative labels used by GPs in Australia: a qualitative interview study - Michelle Guppy; Esther Joy Bowles; Paul Glasziou; Jenny Doust (BJGP Open)
Background: Guidelines for terminology defining chronic kidney disease (CKD) have been in use for 20 years. Age is not currently considered in the guideline definition of CKD. In previous studies, GPs have been reluctant to give older patients the label of CKD. Aim: To determine what language GPs are using to describe or label CKD with their older patients, and to explore the reasons for their use of alternative language. Design & setting: This was a descriptive qualitative interview study of Australian GPs. Method: Twenty-seven GPs were recruited via email and interviewed regarding their management of CKD. GPs were asked what language and terminology they used when discussing a diagnosis of CKD with their older patients. Results: 'Labelling of CKD', the language that GPs use when talking about CKD with their patients, emerged as a major theme from the initial GP interviews. Sub-themes emerged, including types of alternative labels and rationale for alternative labels. GPs used descriptions of 'reduced kidney function' to explain CKD to their patients, either in parallel with the diagnosis of CKD or instead of it. GPs had concerns about the words 'chronic' and 'disease', and used different terminology to explain these words to patients when diagnosing them with CKD. Conclusion: GPs use alternative descriptions to explain mild decrease in kidney function with older patients. Alternative labels that denote level of risk to older patients, without creating unnecessary concern about normal age-related kidney function, need to be explored.